CORRELATION OF RICE PRODUCTIVITY, AMOUNT OF ACTIVE TEMPERATURE AND PRECIPITATION IN THE ROSTOV REGION - Р. I. Kostylev; Е. V. Krasnova; A. А. Redkin; Yu. Р. Kalievskaya; М. V. Teslya (Зерновое хозяйство России, 2018)
The article has presented the results of the comparative analysis of rice productivity in the Rostov region and FSTI “Proletarskoe” and weather conditions in the period of rice vegetation from May to September. Due to the correlation and regressive analysis we have determined the effect of the amount of biologically active air temperatures (BAT) and the amount of precipitations during rice growing on its productivity. The researches and statistic processing of the yield data have been done among five rice-growing parts of the Rostov region. The data about rice production were received from the Ministry of Agriculture and Food of the Rostov region. The samples of the control farm were studied in the laboratory of rice-growing in ARRIGC. The interrelation of rice productivity, temperature regime and precipitations during the vegetation period were analyzed from 2001 till 2015. The results of the study showed that the air temperature during the vegetation period greatly influenced on rice productivity, and increased it on 0.32-0.34 t/ha with the improvement of heat supply on every 100ºС. The precipitations negatively influenced on rice productivity. Every 100 mm of them reduced rice productivity on 0.74 t/ha in the Rostov region and on 0,68 t/ha in “Proletarskoe”. As the climate in the Rostov region became dryer and hotter during the last years, it became possible to grow the varieties with longer period of vegetation, than before. Thus the choice of the varieties and agrotechnical methods of their cultivation in the Rostov region should be directed to the efficient use of temperature resources, especially at the beginning and at the end of the vegetation period.